Methicillin-resistant Staphylococcus aureus Colonization and Pre- and Post-hospital Discharge Infection Risk. (11th August 2018) - Nelson, Richard E; Evans, Martin E; Simbartl, Loretta; Jones, Makoto; Samore, Matthew H; Kralovic, Stephen M; Roselle, Gary A; Rubin, Michael A
Abstract : We used Veterans Affairs data to estimate the relationship between MRSA colonization and pre- and postdischarge MRSA infections. We found that MRSA colonization significantly increases the risk of MRSA infection and that a substantial proportion of MRSA infections occur after discharge. Abstract: Background: The Department of Veterans Affairs implemented an active surveillance program for methicillin-resistant Staphylococcus aureus (MRSA) in 2007 in which acute care inpatients are tested for MRSA carriage on admission, unit-to-unit transfer, and discharge. Using these data, we followed patients longitudinally to estimate the difference in infection rates for those who were not colonized, those who were colonized on admission (importers), and those who acquired MRSA during their stay. We examined MRSA infections that occurred prior to discharge and at 30, 90, 180, and 365 days after discharge. Methods: We constructed a dataset of 985626 first admissions from January 2008 through December 2015 who had surveillance tests performed for MRSA carriage. We performed multivariable Cox proportional hazards and logistic regression models to examine the relationship between MRSA colonization status and infection. Results: The MRSA infection rate across the predischarge and 180-day postdischarge time period was 5.5% in importers and 7.0% in acquirers without a direct admission to the intensive care unit (ICU) and 11.4% in importers and 11.7% in acquirers who were admitted directly to the ICU. The predischarge hazard ratio for MRSA infection was 29.6 (95% confidence interval [CI], 26.5–32.9) for importers and 28.8 (95% CI, 23.5–35.3) for acquirers compared to those not colonized. Fully 63.9% of all MRSA pre- and postdischarge infections among importers and 61.2% among acquirers occurred within 180 days after discharge. Conclusions: MRSA colonization significantly increases the risk of subsequent MRSA infection. In addition, a substantial proportion of MRSA infections occur after discharge from the hospital.